The cold adaption profiles of Pseudoalteromonas shioyasakiensis D1497 from Yap trench to cope with cold - Jingjing Duan; Wenbin Guo (Biotechnology Reports, 2021)
Genome sequencing of Pseudoalteromonas shioyasakiensis D1497, a psychrophile from the Yap trench, revealed that it contained a circle chromosome of 3,631,285 bp with 40.94% GC content and prefered to use codons with A/T in the third position. Additionally, the relative synonymous codon usage (RSCU) values indicated the codons with A and T in the third position were always the most used. Cultivation of P. shioyasakiensis D1497 presented lower substrate consumption rate, higher ATP pool and higher conversion rate of biomass per unit substrate consumed at low temperature (15 °C) than that of the room temperature (25 °C) culture. Comparative transcriptomic analysis revealed that the mRNA abundance of energy metabolism related genes was decreased in 15 °C culture compared with that of 25 °C culture. In addition to its codon usage biases profile, P. shioyasakiensis D1497 presented an energy saving metabolism strategy to cope with cold, converting more carbon source into biomass in cold environment.